2021
DOI: 10.1186/s13102-021-00360-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 1-year intervention comprising brief counselling sessions and low-dose physical activity recommendations in Japanese adults, and retention of the effect at 2 years: a randomized trial

Abstract: Background In an effort to increase people’s adherence to active lifestyles, contemporary physical activity (PA) guidelines now include low-dose PA. Methods PA was evaluated in 583 participants of the Nutritional and Physical Activity Intervention Study (NEXIS) cohort (30–65 years old); 349 inactive participants (MVPA, 2.7 ± 1.0 MET-h/day) were randomly assigned to the intervention or control groups, and 235 active participants participated in foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…We included 115 people (30 men and 85 women; mean and SD of age were, 55.3 ± 8.0 years old, and range of age was 32–69 years old). Participants were recruited from a longitudinal study at the National Institute of Health and Nutrition, Tokyo 45 . The inclusion criteria were as follows: (1) anthropometric variables were measured.…”
Section: Methodsmentioning
confidence: 99%
“…We included 115 people (30 men and 85 women; mean and SD of age were, 55.3 ± 8.0 years old, and range of age was 32–69 years old). Participants were recruited from a longitudinal study at the National Institute of Health and Nutrition, Tokyo 45 . The inclusion criteria were as follows: (1) anthropometric variables were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a significant proportion of the participants retained active behaviors until 1 year after the intervention. [ 27 ] In a study it was shown that circuit training once per week over 32 weeks prevented the aging-related decline of CRF in previously sedentary subjects and reduced systolic BP during submaximal exercise, indicating improved exercise tolerance. [ 28 ] A study concluded that physical activity of diabetes patients with hypertension is needed to control the level of blood glucose and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent inactivity was defined as the sum of sedentary (< 1.5 METs) and non-wearing time and calculated as 1440 − (LPA + MVPA) based on previous studies 45 . These PA intensity categories have been commonly used in previous studies using the same device 43 , 46 , 47 . In our study, we used an accelerometer that does not have the capability of distinguishing among the sedentary time, sleep time, and non-wearing time (such as during bathing or swimming).…”
Section: Methodsmentioning
confidence: 99%